Perspective: Linkage Maps, Communities of Geneticists, and Genome Databases. Issue 2 (1st October 2020) - Botstein, David
Abstract: The Thomas Hunt Morgan Medal recognizes lifetime contributions to the field of genetics. The 2020 recipient is David Botstein of Calico Labs and Princeton University, recognizing his multiple contributions to genetics, including the collaborative development of methods for defining genetic pathways, mapping genomes, and analyzing gene expression.